Pengaruh Penerapan Standar Akuntansi Pemerintah Dan Good Governance Terhadap Kualitas Laporan Keuangan Pemerintah Kabupaten Ogan Komering Ilir - Nurdyah Kusuma Putri; Bainil Yulina; Firmansyah Firmansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of the implementation of Government Accounting Standards and Good Governance on the Quality of Financial Reports of the Regional Government of Ogan Komering Ilir. This research uses a quantitative approach. Data were collected through the distribution of questionnaires to 159 respondents who are financial management officials within the Regional Work Units (OPD) of Ogan Komering Ilir Regency. The data were analyzed using multiple linear regression with the help of SPSS version 25. The results of the study show that both the implementation of Government Accounting Standards and Good Governance have a positive and significant influence on the quality of financial reports. This research emphasizes that the synergy between the implementation of accounting standards and good governance is an important factor in improving the quality of regional financial reporting.